Well-Being and Trauma in Adults Displaced by Political Violence - Abello Llanos, Raimundo; Universidad del Norte (Pontificia Universidad Javeriana, 2009)
This study studied Subjective and Objective Psychological Well-being, and Fatalism, Trauma and Irrational Posttraumatic Cognitions, in adults displaced by socio-political violence, living in Barranquilla, Colombia. Outcomes suggest that people who have been victims of forced displacement exhibit undeniable symptoms of psychosocial trauma, and that they also have elements associated to Mental Health